Meningkatkan Kemampuan Public Speaking pada Anak di Panti Asuhan Melalui Pendekatan Latihan Mandiri dan Lingkungan Sosial - Patty, Elyakim Nova Supriyedi (EMPOWERMENT: Journal of Community Practice, 2025)
This service program aims to improve the public speaking skills of children at the Patmos Orphanage through an approach that involves independent training, educational games, and social support from Bumigora University students who are members of UKM Oikumene. The methods used in this program include the delivery of material through presentations, questions and answers, and active games such as marbles relays on a spoon, chain stories, and guessing styles. The program involved 30 children as participants who were guided by students to develop public speaking skills. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the service showed that this approach was effective in helping children be more confident in speaking in front of others, both in informal and formal contexts. The involvement of students as facilitators provides social support that strengthens the learning process, so that children feel more comfortable and excited in practicing. The novelty of this research lies in the application of fun and interactive methods to develop soft skills of children in orphanages. This program contributes to the development of children's communication skills as part of efforts to improve the quality of human resources in Indonesia